1980
DOI: 10.1111/j.1095-8649.1980.tb02774.x
|View full text |Cite
|
Sign up to set email alerts
|

An energy budget for juvenile thick‐lipped mullet, Crenimugil labrosus (Risso)

Abstract: A series of experiments were carried out to construct an energy budget for juvenile thicklipped mullet, Crenimugil lahrosus Risso. A partial factorial experimental design was used to cxamine the effects of temperature, fish size and meal size on growth. The maximum ration that the fish were able to ingest completely per day was found to be 0.8, 1.4 and 2.3% wet body weight (R.w.) at 13,18 and 23" C, respectively. Ingested maintenance requirements (M.R.) were estimated to be 137, 205 and 288 cal fish-' day-' at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Hepher (1988) collected data from 45 species including five exceptions with exponents of one or so. Cui & Liu (1990) found 0.999 for Pseudobagrus fulvidraco (Richardson) whilst the maintenance requirement, which can be compared to routine energy expenditure, of thick-lipped mullet, Crenimugil labrosus (Risso) scaled with an exponent of 1.04 (Flowerdew & Grove, 1981). Over the small range of weight analysed, no scaling for body weight is apparent for our grass carp.…”
Section: Discussionmentioning
confidence: 85%
“…Hepher (1988) collected data from 45 species including five exceptions with exponents of one or so. Cui & Liu (1990) found 0.999 for Pseudobagrus fulvidraco (Richardson) whilst the maintenance requirement, which can be compared to routine energy expenditure, of thick-lipped mullet, Crenimugil labrosus (Risso) scaled with an exponent of 1.04 (Flowerdew & Grove, 1981). Over the small range of weight analysed, no scaling for body weight is apparent for our grass carp.…”
Section: Discussionmentioning
confidence: 85%
“…They partitioned energy from the high protein and high lipid pellets in a similar way to carnivorous species fed pelleted diets. Respiration ( 2 8 4 6 % of consumed energy) and production (18-33%) were found in individual Crenimugil labrosus (Risso) with gross growth efficiencies of over 15% (Flowerdew & Grove, 1980) and compare with our range for grass carp (Table VI). Cui & Liu (19904 constructed average energy budgets for six teleost species fed ad libitum (at approximately the maximum daily intake) and found that R was always the largest component (50-69% of consumed energy) whereas P was much smaller (21-35%).…”
Section: Venkatachalammentioning
confidence: 90%
“…Digestive assimilation efficiency is the ratio of energy assimilated to energy ingested (Flowerdew and Grove ), which indicates how much energy of the consumed food can be utilized. To determine DE of adults, we followed Kotrschal et al.…”
Section: Methodsmentioning
confidence: 99%
“…The rest of the sample (12 mg [range: 2–28 mg]) was used to determine energy content; we determined energy content (J/g) from food and feces by bomb calorimetry using an adiabatic calorimeter (IKA 4000, Janke & Kunkel, Staufen, Germany) with a microbomb insert. Following Flowerdew and Grove (), DE was calculated as: Efficency (%)=100×normalCr2O3/ Energ y food normalCr2O3/ Energ y faeces .…”
Section: Methodsmentioning
confidence: 99%